Peri-Urban Livelihood and Adaptive Capacity: Urban Development in Dar Es Salaam - Ricci, Liana (Consilience, 2012)
This research focuses on the interactions between urban development and global environmental change processes as crucial for reducing the impacts of climate change. Together with the challenges of rapid urban growth, environmental change impacts will undermine efforts to achieve sustainable development. Peri-urban refers to the area where urban and rural features and processes meet, intertwine and interact, usually located between city and countryside. Peri-urban growth patterns are shaping most of the urban development in sub-Saharan Africa, raising concerns regarding vulnerability to global environmental change in unplanned settlements. To date, there has been little exploration of the implications of peri-urban patterns for social vulnerability and adaptation options. The study discussed in this paper, conducted in Dar es Salaam, Tanzania, illustrates the livelihood strategies and environmental management practices used by peri-urban dwellers, while underlining challenges and opportunities for adaptive capacity. According to a few scholars, the acknowledgement of such hybridity leads to a reconsideration of the dominant strategies for addressing environmental issues in peri-urban areas. Assuming the transition to urban is the best solution, those strategies emphasize the role of infrastructure and services provisioning. Moreover, a criticism of dominant approaches arises through analysis of the recent trend toward ecological security in global cities’ environmental management.